Why do we hurt ourselves? : understanding self-harm in social life - Brossard, Baptiste, 1985- (Indiana University Press, 2018)
Why does an estimated 5% of the general population intentionally and repeatedly hurt themselves' What are the reasons certain people resort to self-injury as a way to manage their daily lives' In Why Do We Hurt Ourselves, sociologist Baptiste Brossard draws on a five-year survey of self-injurers and suggests that the answers can be traced to social, more than personal, causes. Self-injury is not a matter of disturbed individuals resorting to hurting themselves in the face of individual weaknesses and difficulties. Rather, self-injury is the reaction of individuals to the tensions that compose, day after day, the tumultuousness of their social life and position. Self-harm is a practice that people use to self-control and maintain order'to calm down, or to avoid "going haywire" or "breaking everything." More broadly, through this research Brossard works to develop a perspective on the contemporary social world at large, exploring quests for self-control in modern Western societies.